Nursing diagnosis after hematopoietic stem cell transplant due to Fanconi anemia - Lara Cássia Silva Sandri; Letícia Pontes; Carmem Maria Sales Bonfim; Solena Ziemer Kusma (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify nursing diagnoses in patients who underwent hematopoietic stem-cell transplants due to Fanconi anemia, according to the NANDA-I taxonomy. Methods: exploratory study using a retrospective analysis of 85 records from patients who underwent hematopoietic stem-cell transplants due to Fanconi anemia, developed in a specialize transplant center in the South of Brazil. The results were analyzed using descriptive statistics. Results: 73 different diagnoses were found in 9 out of the 13 domains from the NANDA-I taxonomy. From these, 22 were in 50% or more of the patients investigated, and most of them are related to the domain Safety/Protection. Conclusions: it was possible to identify the nursing diagnosis in the patients who underwent hematopoietic stem cell transplants due to Fanconi anemia, contributing to design a plan for the care of these patients. The same was true for those with other syndromes of chromosomal instability that need to undergo this transplant.